1993
DOI: 10.1246/cl.1993.1939
|View full text |Cite
|
Sign up to set email alerts
|

One-Photon Ionization of Liquid Water upon 193 nm Laser Irradiation

Abstract: Water was photoionized through a one-photon process upon 193 nm laser irradiation. The quantum yield of photoionization was a few percent. Multiphoton ionization was not observed in this work, up to the laser fluence of 1.6 J/cm2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…The present study provides more precision at the lower excitation energies because multiple shots could be averaged. The one-photon quantum yield at 193 nm 25 that the "quantum yield of ionization was a few percent". We are also in agreement with the original report of Boyle et al, 1 who estimated a quantum yield on the order of 0.005 near the absorption edge (but who suggested that the threshold for ionization was 6.5 eV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study provides more precision at the lower excitation energies because multiple shots could be averaged. The one-photon quantum yield at 193 nm 25 that the "quantum yield of ionization was a few percent". We are also in agreement with the original report of Boyle et al, 1 who estimated a quantum yield on the order of 0.005 near the absorption edge (but who suggested that the threshold for ionization was 6.5 eV).…”
Section: Resultsmentioning
confidence: 99%
“…At 25°C, equivalent conductivites for F -and HSO 3 -ions are 54.7 and 50 Siemen cm 2 /mole, respectively. 22 These numbers were corrected for temperature (recorded during each measurement) by dividing by the ratio of viscosities η(t)/η (25). A similar assumption (conductivity proportional to viscosity) was made to correct the specific conductivities of these ions for heavy water.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][23][24][25] This is surprising since the ionization potential of the gas-phase molecule is much higher ͑12.6 eV͒. 26,27 Correcting the gasphase ionization threshold for the electronic polarization energy of liquid water and the minimum energy of the ''quasifree'' electron leads to a Born-Oppenheimer ionization threshold higher than 8.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…The plots were fitted by the straight lines with slopes of 1.4 ( 0.2 and 3.2 ( 0.5 for ArF and KrF lasers, respectively. The slopes in Figure 2 larger than 1 and 2, which are expected for formation of a hydrated electron with ArF and KrF lasers, 13 suggested that the carboxylic group is formed not only by photoionization of water but also by a secondary photoreaction. 17 A possible mechanism for the present surface photoreaction is depicted in eqs 1-8: photoionization of water (1); capture of a hydrated electron by the fluoropolymer (2); elimination of a fluoride ion from the fluoropolymer radical anion (3 and 4); attack of the • OH radical on the radical site on the polymer (5 and 6); elimination of HF from alcohols giving a carboxylic or ketone group (7 and 8).…”
mentioning
confidence: 82%
“…12 The present result is almost in good accordance with the reported value of 1-2 µs. 13 PTFE has no absorption at >180 nm, whereas water has an onset of absorption around 190-200 nm. 14 Essentially, this will be the same for other fluoropolymers and excitation of water can be expected for the irradiation at 185 and 193 nm.…”
mentioning
confidence: 99%